O Povoado do Carrascal (Oeiras). Estudo das ocupações do Neolítico Final e do Calcolítico. - Cardoso, João Luís (2015)
In this article we present the Late Neolithic occupation of Carrascal’s settlement and discuss its functional feature. We conclude that it is a settlement with mixed carachteristics, corresponding to a specialized lithic workshop, located nearby the raw material resources, simultaneously with important evidence of semi-permanent, or even permanent, human occupation evidenced by the ceramics and polished stone industry.